Identifying Protein Function—A Call for Community Action - Roberts, Richard J (Public Library of Science, 2004)
Functional information is lacking for many of the hypothetical proteins encoded within sequenced genomes. Richard Roberts proposes that a community-based approach might offer an effecient way to fill the function gap